Forecasting the workforce needs of the Australian rail transport industry (ARTI) - Mahendran, Anusha; Dockery, Alfred Michael (Planning and Transport Research Centre (PATREC), 2008)
Current and emerging skills shortages within the Australian rail transport industry (ARTI) are increasingly being reported. Like many other industries, the rail sector is also having to contend with an aging workforce and further labour shortages that are likely to result from the imminent retirement of senior staff and older workers. The ARTI’s heavy reliance on the skills of its personnel therefore means that such labour issues are likely to have important implications for the industry’s prospective output capacity. The development of accurate forecasting models to predict likely future trends relating to labour resources within the ARTI would therefore greatly assist the sector to anticipate its future skills needs. This paper hopes to contribute to this endeavour by presenting forecasts of future labour supply and demand within the ARTI, disaggregated by occupation. The projections are derived through a production function model which differentiates between the main occupational categories of labour as inputs, and with outputs based upon existing projections of freight and passenger transport task. Projected labour shortages and the average ages of rail workers within specific occupational groups are also determined and examined. The modelling assumptions are based on data and trends derived from primary research acquired from rail operators across the country, existing literature as well as the most recently available ABS statistics.